Innovation model sirukogalar (system reference communication three pillars) in primary mental health services for end practice stocks - Saimi, Saimi; Sudiarsini, Nita (Institute of Computer Science (IOCS), 2024)
Practice stocks or restrictions movement in individuals with disturbance soul Still become problem serious in many communities, especially in deprived areas develop. Study This try For dissect the model or system new , that is Sirukogalar , which combines elements innovative in communication inter -pillar for increase effectiveness service health primary soul. This Study aim For explain How framework Sirukogalar model working and its effectiveness in lower number stock . Study This use approach studies case . Study carried out at RSJ Mutiara Sukma NTB. Research result show that framework Sirukogalar model work is system services that rely on collaboration between RSJ Mutiara Sukma, Puskesmas and families patient . Through system reference communication three pillars, more collaboration Good so that can give service health a holistic and coordinated soul. Application of the Sirukogalar model proven effective lower number marked stakes​ with the more decreasing number patient stocks from 2019-2023 in NTB